2019
DOI: 10.21873/invivo.11795
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin and Syndecan-1 Expression in Patients With Advanced Non-small Cell Lung Cancer Treated With Chemoradiotherapy

Abstract: Background/Aim: The aim of the study was to investigate whether E-cadherin and syndecan-1 are molecular markers of advanced non-small cell lung cancer (NSCLC). Patients and Methods: The expression of E-cadherin and syndecan-1 (SDC1) was examined immunohistochemically on tissue specimens of 64 patients, with stage III disease at presentation. The obtained expression data were correlated with clinical parameters. Results: Negative expression of SDC1 was correlated with squamous histology (p=0.002). Ecadherin pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Again, consistent with TCGA data, high protein staining of E-cad in kidney renal papillary cell carcinoma was associated with worse prognosis, and no association was detected for kidney renal clear cell carcinoma (96). Recent analysis of E-cad in the cohort of NSCLC with 66% cases representing squamous cell carcinoma identifies E-cad as a positive prognostic factor consistent with TCGA data (97).…”
Section: Expression Of Molecules Involved In the Ctc Cluster Formatio...supporting
confidence: 76%
“…Again, consistent with TCGA data, high protein staining of E-cad in kidney renal papillary cell carcinoma was associated with worse prognosis, and no association was detected for kidney renal clear cell carcinoma (96). Recent analysis of E-cad in the cohort of NSCLC with 66% cases representing squamous cell carcinoma identifies E-cad as a positive prognostic factor consistent with TCGA data (97).…”
Section: Expression Of Molecules Involved In the Ctc Cluster Formatio...supporting
confidence: 76%
“…ICAM‐1 might be a target molecule for NIR‐PIT against other cancers that express it. Previous studies showed that ICAM‐1 expression was detected in 41%, 50%, and 44% of non‐small‐cell lung cancers, 33 gastric cancers, 34 and colorectal cancers 35 . Further research is necessary to evaluate the therapeutic efficacy of ICAM‐1‐targeted NIR‐PIT in mouse models of these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of expression of E-cadherin in the spindle and giant cell epithelial component in resection materials may explain the invasive potential and increase of their metastases of these Ts. TKI (Tyrosine Kinase Inhibitors) is frequently used in the treatment of NSCLC and EMT is believed to play an important role in resistance to these drugs (20,21). Some studies have shown that EMT is involved not only in determining the prognosis of patients with NSCLC, but also in response to specific treatments such as anti-EGFR treatments used for this type of T (22).…”
Section: Discussionmentioning
confidence: 99%